Testing Metabolic Theory of Ecology on the local scale: a preliminary study - Danyłow, Alexia; Ulrich, Werner; Ilieva-Makulec, Krassimira; Olejniczak, Izabella; Hajdamowicz, Izabela; Stańska, Marzena; Uvarov, Alexei (Ecological Questions, 2012)
Data on the density and the body mass of a single community of soil fauna were collected and metabolic rates were calculated from the literature data to test some predictions of the metabolic theory of ecology on the local scale. Part of the results are in accordance with the theory: power functions were found between the metabolic rate and the body mass, and between the density and the body mass. These two relationships have opposite exponents inducing that total population energy use is independent of the body mass. However, the exponents of the relationships were significantly different from the predicted values of |3/4|. The metabolic rate - body mass relationships yielded an exponent >0.8, while the density - body mass relationships yielded an exponent <-0.85. Our results indicate that the metabolic theory of ecology does not hold at the local level. Few studies have been carried out on the local scale and further analysis is required to validate this controversial but promising theory.